The Role of The School Principal in Improving Teacher Performance and School Quality - J. Nabiel Aha Putra; Baharuddin Baharuddin; Agus Maimun; Abd. Haris; Ahmad Barizi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This research aims to describe 1) the role of school principals in improving teacher performance and 2) describe the role of school principals in improving school quality. The method used in this research is a descriptive qualitative approach. Data collection techniques in this research are interviews, observation, and documentation. The results obtained from this research are 1) the role of school principals in improving teacher performance and school quality, by explaining, organizing, actuating, or controlling. Because it has a tremendous effect on progress and improvements for the institution itself. Teacher performance still has to be improved, it doesn't have to be continuously pushed by the school principal. However, the teacher's duties or rights and obligations have been prepared, as to what steps the teacher must take so that the principal only supervises. 2) school quality, every point of its vision and mission is well implemented. So, the rules for educators and students are all clearly stated. So in the end, the quality of the school can be seen from the institution that produces how many and what graduates enter state and foreign universities.